Pengaruh Environmental Responsibility dan Green Innovation Terhadap Nilai Perusahaan - Shelin Cristian; Siti Khairani (Universitas Multi Data Palembang, 2026)
This study aims to examine the effect of Environmental Responsibility and Green Innovation on firm value. The research employs a quantitative approach using secondary data obtained from companies' annual and sustainability reports. The sampleconsistst of 92 observations selected through purposive sampling, and the data are analyzed using multiple linear regression. The findings indicate that Environmental Responsibility has a significant effect on firm value, while Green Innovation does not. However, simultaneously, Environmental Responsibility and Green innovation have a significant influence on firm value.